An investigation into the effects of partial discharge activity in sulphurhexafluoride gas on liquid insulation - Ruffini, Antonio Guido (My University, 2015)
The purpose of the work presented here was to investigate the affects of SPg gas present in insulating liquids. This research was carried out mainly by means of experimental work. Investigations involving the gas evolving or absorbing properties of air and SFg saturated ins;'ating liquids were carried out. These tests showed that the liquids investigated (transformer oil and silicone liquid) were capable of absorbing large amounts of SFg. Further experiments were performed to discover what influence this would have on stressed, enclosed liquid samples with air gaps above them. In addition to this, partial discharges in gas bubbles trapped behind paper insulation were investigated under high voltage stresses. These comparative experiments were done using SFg and N; bubbles. The results obtained have provided evidence that SFg present in liquid insulation is not deleterious to the insulation when compared with the presence of non electronegative gasses.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg 1992